Eine Eskimofrau in Fettagskleidung : [ca. 1901] - Schmitt, Christian, 1868-1933. (2001)
Black and white photograph of an Inuit woman in festive clothing, circa 1901. Black and white photograph of an Inuit woman in festive clothing, circa 1901.